Современные тенденции развития монтажно-сварочных работ - Белоев, М. (Автоматическая сварка, 2008)
The paper describes the modern welding technologies used in site works in construction of main pipelines, pumping and
compressor stations, technological pipelines in power engineering and chemistry, large-sized structures.